Understanding primate brain evolution - Dunbar, R; Shultz, S (Royal Society, 2007)
We present a detailed reanalysis of the comparative brain data for primates, and develop a model using path analysis that seeks to present the co-evolution of primate brain (neocortex) and sociality within a broader ecological and lifehistory framework. We show that body size, BMR and lifehistory act as constraints on brain evolution, and through this influence the coevolution of neocortex size and group size. However, they do not determine either of these variables, which appear to be locked in a tight coevolutionary system. We show that, within primates, this relationship is specific to the neocortex. Nonetheless, there are important constraints on brain evolution: we use path analysis to show that, in order to evolve a large neocortex, a species must first evolve a large brain to support that neocortex, and this in turn requires adjustments in diet (to provide the energy needed) and lifehistory (to allow sufficient time both for brain growth and for “software” programming). We review a wider literature demonstrating a tight coevolutionary relationship between brain size and sociality in a range of mammalian taxa, but emphasise that the social brain hypothesis is not about the relationship between brain/neocortex size and group size per se; rather, it is about social complexity, and we adduce evidence to support this. Finally, we consider the wider issue of how mammalian (and primate) brains evolve in order to localise social effects.